2015
DOI: 10.1038/aps.2014.170
|View full text |Cite
|
Sign up to set email alerts
|

Herbal prescription Chang'an II repairs intestinal mucosal barrier in rats with post-inflammation irritable bowel syndrome

Abstract: Aim: The herbal prescription Chang'an II is derived from a classical TCM formula Tong-Xie-Yao-Fang for the treatment of liver-qi stagnation and spleen deficiency syndrome of irritable bowel syndrome (IBS). In this study we investigated the effects of Chang'an II on the intestinal mucosal immune barrier in a rat post-inflammation IBS (PI-IBS) model. Methods: A rat model of PI-IBS was established using a multi-stimulation paradigm including early postnatal sibling deprivation, bondage and intrarectal administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Many studies regarding natural herbal medicines have demonstrated the therapeutic potential of natural products in intestinal barrier function protection [17, 18]. Furthermore, our previous studies have demonstrated that KIOM-MA/MA18 have anti-inflammatory, anticancer, and antiatopic effects [1315].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies regarding natural herbal medicines have demonstrated the therapeutic potential of natural products in intestinal barrier function protection [17, 18]. Furthermore, our previous studies have demonstrated that KIOM-MA/MA18 have anti-inflammatory, anticancer, and antiatopic effects [1315].…”
Section: Discussionmentioning
confidence: 99%
“…5 Quinolizidine alkaloids of matrine-type were isolated from the roots and rhizomes of S. tonkinensis and have showed potent anti-hepatitis B virus (HBV) activity with an inhibitory potency against hepatitis B surface antigen HBsAg. 31 Wang and his co-authors 43 have suggested that the alkaloids belongs to this class when combined with thymopolypeptides, they could inhibit HBV DNA replication, and further promote the antiviral effect by promoting the expression of IFN-α. 43 Therefore, in our present study, the high activity of EaE fraction may be attributed to the synergistic in its biological activity, including in vitro antiviral and immunomodulatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…31 Wang and his co-authors 43 have suggested that the alkaloids belongs to this class when combined with thymopolypeptides, they could inhibit HBV DNA replication, and further promote the antiviral effect by promoting the expression of IFN-α. 43 Therefore, in our present study, the high activity of EaE fraction may be attributed to the synergistic in its biological activity, including in vitro antiviral and immunomodulatory activities. 43 Many studies have reported that flavonoids isolated from Sophora root act as antibacterial, anti-inflammatory and immunoregulatory.…”
Section: Discussionmentioning
confidence: 99%
“…The CD4 + /CD8 + ratio has been recognized as an important indicator for evaluating the state of immunomodulation and response to homeostasis of the intrinsic immune system (23). Previous studies have shown that the increased CD4 + /CD8 + ratio has been observed in many autoimmune diseases such as SLE (24), inflammatory bowel disease (25) and multiple sclerosis (26). A low CD4 + /CD8 + ratio was considered as a marker of decreased immune function (27), which could result in increasing the risk of HIV-infected, pulmonary tuberculosis and even some tumors (28,29).…”
Section: Discussionmentioning
confidence: 99%